1997
DOI: 10.1002/art.1780400517
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of murine collagen‐induced arthritis in the knee and ipsilateral paw by local expression of human interleukin‐1 receptor antagonist protein in the knee

Abstract: Objective. To determine the efficacy of local human interleukin-1 receptor antagonist (HuIL-1Ra) gene therapy in murine collagen-induced arthritis (CIA).Methods. DBN1 mice were immunized against bovine type I1 collagen. Before the onset of arthritis, NIH/3T3 fibroblasts transfected with pMFG-IRAP were transplanted into the knee cavity. Normal NIH/3T3 cells served as controls. Paws were evaluated macroscopically for redness, swelling, and deformities during the course of arthritis. Swelling of the knee joints w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(85 citation statements)
references
References 17 publications
4
81
0
Order By: Relevance
“…Similar observations have been made after intra-articular treatment of CIA with IL-1 receptor antagonist, which also results in amelioration of the CIA in the distal paws of treated mice. 25,26 Whether these effects are the result of a direct local inhibition of cytokine spillover and antigen release by reduced inflammation or caused by leakage of IL18BPc to distal joints remains to be established. When comparing incidence versus severity in the distal paws of IL-18BP-treated animals, IL-18 significantly reduced incidence while increase in severity of affected hind paws could not be halted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar observations have been made after intra-articular treatment of CIA with IL-1 receptor antagonist, which also results in amelioration of the CIA in the distal paws of treated mice. 25,26 Whether these effects are the result of a direct local inhibition of cytokine spillover and antigen release by reduced inflammation or caused by leakage of IL18BPc to distal joints remains to be established. When comparing incidence versus severity in the distal paws of IL-18BP-treated animals, IL-18 significantly reduced incidence while increase in severity of affected hind paws could not be halted.…”
Section: Discussionmentioning
confidence: 99%
“…24 Therefore, in some situations it appears preferable to choose local instead of systemic treatment. Studies by Bakker et al 25,26 already showed functionality of local intra-articular therapy for arthritis using IL-1 receptor antagonist.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of IL-1Ra, either systemically or locally by gene transfer, reduces inflammation and joint damage in animal models of RA (20)(21)(22)(23). A recombinant form of human IL-1Ra, anakinra (recombinant methionyl human IL-1 receptor antagonist [r-metHuIL-1ra]), is a competitive antagonist of IL-1 that blocks the actions of IL-1 without any detectable agonist activity.…”
mentioning
confidence: 99%
“…The 'contralateral effect', that is the administration of the expression vector in one joint to suppress arthritis in distal or contralateral joints, has been reported by many laboratories. [47][48][49][50][51][52] This study, which shows activation of the IL-1/IL-6 enhancer-promoter in the contralateral joints by signals derived from the arthritic joint, suggests that there is crosstalk between joints. Treatment of one joint may interfere with this crosstalk and by this suppresses arthritis in the other contralateral joint.…”
Section: Discussionmentioning
confidence: 99%